Aldehyde Dehydrogenase 2 Lactylation Aggravates Mitochondrial Dysfunction by Disrupting PHB2 Mediated Mitophagy in Acute Kidney Injury - Jiaying Li; Xiaoxiao Shi; Jiatong Xu; Kaiyue Wang; Fangxing Hou; Xiaodong Luan; Limeng Chen (Advanced Science)
Abstract Mitochondrial dysfunction is a crucial event in acute kidney injury (AKI), leading to a metabolic shift toward glycolysis and increased lactate production. Lactylation, a posttranslational modification derived from lactate, plays a significant role in various cellular processes, yet its implications in AKI remain underexplored. Here, a marked increase in lactate levels and pan‐Kla levels are observed in kidney tissue from AKI patients and mice, with pronounced lactylation activity in injured proximal tubular cells identified by single‐cell RNA sequencing. The lactylation of aldehyde dehydrogenase 2 (ALDH2) is identified at lysine 52 (K52la), revealing that ALDH2 lactylation exacerbates tubular injury and mitochondrial dysfunction. Conversely, the ALDH2 K52R mutation alleviates these injuries in HK‐2 cells and adeno‐associated virus‐infected kidney tissues in mice. Furthermore, ALDH2 lactylation can be modulated by upregulating SIRT3 in vivo and in vitro, which reduces ALDH2 lactylation, mitigating tubular injury and mitochondrial dysfunction. Mechanistically, immunoprecipitation‐mass spectrometry analysis demonstrates an interaction between ALDH2 and prohibitin 2 (PHB2), a crucial mitophagy receptor. ALDH2 lactylation promotes the ubiquitination‐proteasomal degradation of PHB2 to inhibit mitophagy and worsen mitochondrial dysfunction. These findings highlight the critical role of endogenous lactate in AKI and propose ALDH2 lactylation as a potential therapeutic target.